ANALISIS KINERJA BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG - Rahmadini, Rizky Masita; Subowo, Ari; Djumiarti, Titik (Journal of Public Policy and Management Review, 2015)
The research intends to describe and analyze the performance of Badan Pelayanan Perijinan Terpadu (BPPT) Kota Semarang. This research uses descriptive qualitative research method.Based on the result of research shows that the performance of Badan Pelayanan Perijinan Terpadu Kota Semarang has not been optimal. It is necessary to be increased furthermore in the aspect of productivity, the quality of services, responsiveness, responsibility, accountability, cooperation, and justice .The conclusion in this research is Badan Pelayanan Perijinan Terpadu Kota Semarang has not been optimal. The obstacles that are faced the limited human resources who master in technology and ineffective coordination with relevant agencies. Based on conclusion, researcher recommends to Badan Pelayanan Perijinan Terpadu Kota Semarang to improve the criteria that is assessed, it is still less successfull so the performance of BPPT Kota Semarang can be optimized.